A Cross-Sectional Study On Refractive Error In Relation To Corneal Curvature Among Adults With Refractive Error In A Tertiary Care Center (Journal of Pharmaceutical Negative Results, 2022)
Background: The most frequent worldwide cause of visual impairment is refractive errors. Important biometric variables impacting refractive errors include changes in axial length (AL) and corneal curvature (CC).Material and Methods: A cross sectional study was conducted among adult patients with refractory error in OPD of Ophthalmology. 400 patients were selected using a convenient sampling technique and they were examined for refraction using an auto refractor and corneal curvature using an auto keratometer. Data were analysed using SPSS software by descriptive and inferential statistics.Results: There was a significant positive correlation between spherical refractory error and corneal curvature on the right side (0.121) and left side (0.211). Conclusion: It might be determining factor among patients with refractive errors for the choice of treatment.